Analysis of the Effectiveness of Using Audio Visual Media in Science Learning in Elementary Schools - Mar'atus Sholihah; Rohmani (Journal of Psychology and Instruction, 2024)
Audiovisual learning tools are utilized in the educational process to deliver subject content by integrating sound and visual elements. This study aims to evaluate the effectiveness of audiovisual media in teaching Natural Sciences (IPA) at the elementary school level. The research method employed is a Systematic Literature Review (SLR), utilizing the Google Scholar database. The literature review was conducted in three stages. Initially, the keyword "Use of audiovisual media" yielded 7,750 documents. In the second stage, adding "science learning" reduced the results to 1,160 documents, and in the final stage, further refining the keyword with "in elementary school" resulted in 648 documents. These documents were then filtered based on specific inclusion criteria, leaving 8 articles for further analysis. The findings indicate that audiovisual learning media positively impacts science education in elementary schools. Moreover, the use of such media can significantly enhance science learning outcomes across both lower and upper grades. Therefore, audiovisual media has been proven to facilitate the science learning process in elementary schools.